Airtraq as an alternative device for airway management for emergency cesarean section in a parturient with kyphoscoliosis and short stature - A case report - K Sathya Narayanan; Geeta Bhandari; Abhishek Nautiyal; Abha Tiwari (Wolters Kluwer Medknow Publications, 2023)
Kyphoscoliosis is a spine abnormality identified by anterior flexion (kyphosis) and lateral curvature (scoliosis) and its causes can be multifactorial. A 24-year-old primigravida with short stature and severe thoracolumbar kyphoscoliosis was scheduled for emergency cesarean section due to non-progression of labor with fetal distress. After failed spinal and unsuccessful conventional laryngoscopy, the patient was intubated using an optical Airtraq (Prodol Meditec S.A., Vizcaya, Spain) laryngoscope and operated. The main purpose of an anesthesiologist is to perform safe and skilled anesthetic management to minimize risk to mother and baby. Kyphoscoliosis exacerbates an already compromised cardiopulmonary status due to pregnancy. The severity of pulmonary impairment depends upon the degree of Cobb's angle. None of the anesthetic techniques is said to be perfect as each technique has its own merits and demerits. General anesthesia may be indicated because of maternal preference or maternal cardiopulmonary disease or technical difficulties related to the regional block. Airtraq can be an alternative option for airway management as it provides a direct view of the glottis in a neutral neck position.